IMMU-12. TGFβ ACTIVATION BY RADIATION OPPOSES IMMUNE REJECTION OF INTRACRANIAL GL261 - Barcellos-Hoff, Mary; Gonzalez-Junca, Alba; Vera, Denis Beckford; VanBrocklin, Henry; Franc, Benjamin; Parry, Renate (Neuro-oncology (Charlottesville, Va.), 2018)
Abstract Enabling anti-tumor immunity in brain is a challenge due to its unique microenvironment that includes tissue-specific extracellular matrix, immune cells and vasculature, and because many glioblastoma patients require rapid treatment, usually surgery followed by radiation therapy, that may oppose immunotherapy. Here we hypothesize that transforming growth factor β (TGFβ) is at the root of the profoundly immunosuppressive tumor microenvironment, and is perpetuated by standard of care, radiation therapy. We first localized TGFβ activation in situ using GC1008, a humanized pan-isoform TGFβ neutralizing antibody, radiolabeled with 89Zr for PET-CT imaging. The antibody localized to a murine intracranial tumor compared to the injury-control brain injected with PBS. Paired comparisons of dual flank tumors in which one was irradiated (15 Gy) showed that radiation significantly increased 89Zr-GC1008 uptake (p0.0002). This was confirmed by immunostaining with an antibody that detects active TGFβ and nuclear pSMAD, indicative of signaling. Administration of TGFβ pan-isoform neutralizing antibody, 1D11 (25 mg/kg), to mice bearing irradiated intracranial tumors reduced immunostaining for active TGFβ and p-SMAD and blocked induction of a critical TGFβ target, tenascin-C, compared to treatment with isotype control antibody. These data support radiation-induction of TGFβ activation. Mice bearing i.c. GL261 (n=10–12) treated with 1D11 compared to isotype IgG had similar (17d vs 16d) median survival, which was doubled by tumor irradiation (10 Gy). Combined treatment with 1D11 and radiation led to durable control (Kaplan-Meier, p>0.0009), in which mice that showed complete regression by bioluminescence imaging for >45 days rejected a flank GL261 re-challenge. TGFβ inhibition with tumors treated with 5 daily 6 Gy fractions also eradicated most intracranial GL261. The undetectable brain bioluminescence and successful re-challenge suggest that TGFβ inhibition in the context of radiation can release the immunosuppressive microenvironment, elicit anti-tumor immunity and enable immune memory.